Sensory Characteristics of Brewing Liberica Coffee (Coffea liberica) at Various Variants and Concentrations of Sweeteners - Salsabhilla, Keisya Aura; Dewi, Yohana Sutiknyawati Kusuma; Lestari, Oke Anandika (Universitas Tanjungpura, 2025)
Coffee is a beverage derived from the extraction of coffee plant seeds that has become one of the most popular drinks in the world. There are 4 (four) main species of coffee including robusta, arabica, liberica, and exelsa. Liberica coffee has a taste that tends to be bitter, thick, and has a low acidity level, the bitter taste in coffee can be minimized by adding sweeteners, sweeteners are food additives added to food and beverages to cause sweetness. This study aims to determine the effect of sweetener variants and concentrations on the physicochemical and sensory properties of brewed Liberika coffee. This research design uses a Randomized Group Design (RAK) with 1 factor, namely sweetener formulation consisting of sucrose and xylitol with 7 levels of treatment. Each treatment was repeated 4 times so that 28 experimental units were obtained. The observation data obtained will be analyzed statistically using Analysis of Variance (ANOVA), if the treatment has a significant effect, then it will be followed by the Honest Real Difference test (BNJ) at the 5% level. Sensory analysis will be carried out using the hedonic test and the data obtained will be analyzed using the Kruskall Wallis method. Determination of the best treatment using the effectiveness index test. The best chemical and sensory characteristics of Liberika coffee brew were obtained with the addition of 20% xylitol, taste sensory value of 3.90, overall liking sensory value of 3.87, body sensory value 3.70 likes, color sensory value 3.73, and aroma sensory value 3.57.